MITIGASI DHCP STARVATION ATTACK PADA ROUTERBOARD MIKROTIK DAN PENGARUHNYA TERHADAP PERFORMANSI - Novianto, Dian; Japriadi, Yohanes Setiawan; Tommy, Lukas; Sujono (Jurnal Ilmiah Informatika Global, 2024)
As people become more dependent on information technology, the need for Internet availability increases. Various types of devices are connected to the network, increasing the convenience of using information technology. However, this convenience can often be disrupted by attacks on the network infrastructure, one of which is a DHCP Starvation attack. The Dynamic Host Configuration Protocol (DHCP) is a client-server-based protocol used to automatically assign or obtain IP addresses for client computers or other network devices. Mitigating DHCP Starvation attacks is one form of protection for users. The impact of this attack is that the attacker can become one of the hosts on the network and perform a man-in-the-middle attack, so the impact of information leakage can occur. In addition, it is necessary to know the impact on router resources when a DHCP Starvation attack occurs, so that network managers can calculate how much resources are needed. The author uses a Filtering method based on Mac address es, ARP, and alerts on the Mikrotik router. In addition, the PPDIOO method is also used to develop this system, which consists of preparation, planning, design, Implementation, operation, and optimization. The test results showed that the application of this Filtering method proved to be very effective in preventing DHCP Starvation attacks, and the router board resources were not significantly affected when this Filtering method was applied.